Loss of miR-101-3p in melanoma stabilizes genomic integrity, leading to cell death prevention - Lämmerhirt, Lisa; Kappelmann-Fenzl, Melanie; Fischer, Stefan; Meier, Paula; Stäbler, Sebastian; Kuphal, Silke; Boßerhoff, Anja Katrin (Cellular & Molecular Biology Letters, 2024)
Malignant melanoma remains the most lethal form of skin cancer, exhibiting poor prognosis after forming distant metastasis. Owing to their potential tumor-suppressive properties by regulating oncogenes and tumor suppressor genes, microRNAs are important player in melanoma development and progression. We defined the loss of miR-101-3p expression in melanoma cells compared with melanocytes and melanoblast-related cells as an early event in tumor development and aimed to understand the tumor suppressive role of miR-101-3p and its regulation of important cellular processes. Reexpression of miR-101-3p resulted in inhibition of proliferation, increase in DNA damage, and induction of apoptosis. We further determined the nuclear structure protein Lamin B1, which influences nuclear processes and heterochromatin structure, ATRX, CASP3, and PARP as an important direct target of miR-101-3p. RNA sequencing and differential gene expression analysis after miR-101-3p reexpression supported our findings and the importance of loss of mir-101-3p for melanoma progression. The validated functional effects are related to genomic instability, as recent studies suggest miRNAs plays a key role in mediating this cellular process. Therefore, we concluded that miR-101-3p reexpression increases the genomic instability, leading to irreversible DNA damage, which leads to apoptosis induction. Our findings suggest that the loss of miR-101-3p in melanoma serves as an early event in melanoma progression by influencing the genomic integrity to maintain the increased bioenergetic demand.
CRIS-Team Scopus Importer:2024-03-15
Keywords: Apoptosis; DNA damage; Genomic integrity; Melanoma; miR-101-3p; miRNA; RNA-seq